Climate and Organizational Culture and its Relationship with the Management Change Traditional Organizations to Smart Organizations - Rodríguez Piñero, Héctor (2018)
This paper is a documentary study, which aims to encompass the principles of climate and organizational culture and its influence on change management, with emphasis on the latter in terms of the fundamental differences between traditional and intelligent organizations. It starts with conception and definition of organizational climate to pass the relating structure to form a culture in the company. In this case the analysis described the change is treated as a result of complex component of organizations in general to fall into what is change, mainly from the perspective of traditional and intelligent organizations, taking into account their relation with respect initially treated components of climate and organizational culture. It closes with a conclusive reflection point that is reflected in the conjunction of three essential components that make up the organizations as complex, dynamic and adaptive systems.